Impacts of zero tillage on soil enzyme activities, microbial characteristics and organic matter functional chemistry in temperate soils - Mangalassery, S.; Mooney, Sacha J.; Sparkes, D.L.; Fraser, W.T.; Sjögersten, Sofie (Elsevier, 2015)
Zero tillage management of agricultural soils has potential for enhancing soil carbon (C) storage and reducing greenhouse gas emissions. However, the mechanisms which control carbon (C) sequestration in soil in response to zero tillage are not well understood. The aim of this study was to investigate the links between zero tillage practices and the functioning of the soil microbial community with regards to C cycling, testing the hypothesis that zero tillage enhances biological functioning in soil with positive implications for C sequestration. Specifically, we determined microbial respiration rates, enzyme activities, carbon source utilization and the functional chemistry of the soil organic matter in temperate well drained soils that had been zero tilled for seven years against annually tilled soils. Zero tilled soils contained 9% more soil C, 30% higher microbial biomass C than tilled soil and an increased presence of aromatic functional groups indicating greater preservation of recalcitrant C. Greater CO2 emission and higher respirational quotients were observed from tilled soils compared to zero tilled soils while microbial biomass was 30% greater in zero tilled soils indicating a more efficient functioning of the microbial community under zero tillage practice. Furthermore, microbial enzyme activities of dehydrogenase, cellulase, xylanase, β-glucosidase, phenol oxidase and peroxidase were higher in zero tilled soils. Considering zero tillage enhanced both microbial functioning and C storage in soil, we suggest that it offers significant promise to improve soil health and support mitigation measures against climate change.